The petrogenesis of the ignimbrites and quartz porphyritic granites exposed along the coast at Saldahna, South Africa - Joseph, Cedric S. A. (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.